The Impact of Contingency Factors on the Sophistication of Costing Systems: Evidence from Tunisia - Hanen Moalla; Achref Mezouel (STIE Malangkucecwara, 2020)
This research investigates the impact of contingency factors on the sophisticationof costing systems in Tunisia. Sophistication is analyzed by using the following criteria:ABC systems, full costing systems, the number of cost pools in the first stage of allocationand the number of cost drivers in the second stage of allocation. Data were collected through a questionnaire next to 68 companies having a costingsystem. Findings show that contingency factors affect the sophistication of costingsystems and that company’s strategy and product diversity are the most important factors.These two contingency factors are related to different dimensions of the sophistication.Moreover, big-sized companies and manufacturing companies are more likely to adoptABC. In addition, the importance of cost information positively affects the use a fullcosting system and companies with high percentages of indirect costs have a greaternumber of cost pools. This piece of research is one of the rare studies dealing with the characteristics ofcosting systems. Previous research dealt basically with ABC and are mainly conducted indeveloped countries. This study adds to knowledge since it is conducted in a developingcountry and investigates the sophistication of costing systems.